(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The article examines structural changes and their impact on improving the efficiency of small businesses and private entrepreneurship and analyzes trends in the development of small businesses and private entrepreneurship in the region and the Namangan region.